2014
DOI: 10.1105/tpc.114.124297
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Whole-Genome Triplication as Revealed by Comparative Genomic Analyses of the Wild RadishRaphanus raphanistrumand Three Other Brassicaceae Species  

Abstract: Polyploidization events are frequent among flowering plants, and the duplicate genes produced via such events contribute significantly to plant evolution. We sequenced the genome of wild radish (Raphanus raphanistrum), a Brassicaceae species that experienced a whole-genome triplication event prior to diverging from Brassica rapa. Despite substantial gene gains in these two species compared with Arabidopsis thaliana and Arabidopsis lyrata, ;70% of the orthologous groups experienced gene losses in R. raphanistru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 75 publications
1
114
0
Order By: Relevance
“…If expression shifts represent a prerequisite for duplicate gene loss (see below), then we may posit that nonadditive expression characterizes early duplicates of genes encoding structural genes, such as ribosomal protein genes, proteasomal protein genes, and transcription factors, at least in Arabidopsis and perhaps its relatives (17,160). Similar patterns of duplicate gene loss and retention are reported for rice, puffer fish, and yeast (139); species of Brassicaceae (123); and species of Paramecium (119), suggesting possible generalities for factors controlling which genes are retained and which are lost from polyploid genomes. However, alternative patterns of gene retention and loss are observed for ancient duplicates in Compositae (13,21), in which structural genes are retained in duplicate and transcription factors are typically singletons.…”
Section: The Role Of Gene Functionmentioning
confidence: 65%
See 1 more Smart Citation
“…If expression shifts represent a prerequisite for duplicate gene loss (see below), then we may posit that nonadditive expression characterizes early duplicates of genes encoding structural genes, such as ribosomal protein genes, proteasomal protein genes, and transcription factors, at least in Arabidopsis and perhaps its relatives (17,160). Similar patterns of duplicate gene loss and retention are reported for rice, puffer fish, and yeast (139); species of Brassicaceae (123); and species of Paramecium (119), suggesting possible generalities for factors controlling which genes are retained and which are lost from polyploid genomes. However, alternative patterns of gene retention and loss are observed for ancient duplicates in Compositae (13,21), in which structural genes are retained in duplicate and transcription factors are typically singletons.…”
Section: The Role Of Gene Functionmentioning
confidence: 65%
“…In particular, it has been reported that organisms that experience genome fractionation (diploidization) after WGD (polyploidization) exhibit nonrandom distribution of genes that are lost during diploidization. That is, genes belonging to specific functional classes, such as ribosomal protein genes and transcription factors, were more often retained in duplicate (16,56,119,123,139).…”
Section: Gene Dosage Balance Hypothesismentioning
confidence: 99%
“…This process is evident from the presence of a large number of pseudogenes and singletons in many organisms that have undergone WGD (Schnable et al, 2009(Schnable et al, , 2011Schmutz et al, 2010;Moghe et al, 2014). However, tens of thousands of duplicated gene pairs are generally retained in paleopolyploid genomes after tens of millions of years of natural selection (Schnable et al, 2009;Schmutz et al, 2010), indicating their functional importance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the genomes of the following crop wild relatives were sequenced: Aegilops tauschii (Jia et al 2013), Arabidopsis lyrata (Hu et al 2011), diploid cotton (Wang et al 2012b), Glycene soja (Kim et al 2010), other wild soybeans (Li et al 2014a), wild radish (Moghe et al 2014), wild tomatoes (Bolger et al 2014b; The 100 Tomato Genome Sequencing Consortium 2014), woodland strawberry (Shulaev et al 2011), and einkorn wheat (Ling et al 2013).…”
Section: Dna Sequencing Other Omics and Synthetic Biologymentioning
confidence: 99%